Sexual and Reproductive Health: How Can Situational Judgment Tests Help Assess the Norm and Identify Target Groups? A Field Study in Sierra Leone - Moussaoui, Lisa Selma; Law, Erin; Claxton, Nancy; Itämäki, Sofia; Siogope, Ahmada; Virtanen, Hannele; Desrichard, Olivier; , Consortium Sierra Leone Red Cross Society (Frontiers in Psychology, 2022)
Sexual and reproductive health is a challenge worldwide, and much progress is needed to reach the relevant UN Sustainable Development Goals. This paper presents cross-sectional data collected in Sierra Leone on sexual and gender-based violence, family planning, child, early and forced marriage, and female genital mutilation using an innovative method of measurement: situational judgement tests (SJTs), as a subset of questions within a larger survey tool. For the SJTs, respondents saw hypothetical scenarios on these themes and had to indicate how they would react. The objective is to give an impression of beliefs and norms on specific behaviors, which provide insights for social and behavior change interventions. Data was collected by enumerators travelling to villages randomly selected in six districts of the country. The sample is composed of 566 respondents. Results show that female genital mutilation in particular seem to be a priority topic, in comparison to the other topics for which the norms seem to be stronger against those practices. Age differences emerged and suggest priority groups to be targeted (e.g., on the topic of female genital mutilation, younger female respondents and older male respondents gave the lowest coded responses which reflected to less appropriate behaviour in our coding). In terms of validity of the measurement methods, situational judgement test answers correlated positively with other items in the survey, but the magnitude of the association is often small, and sometimes not significant. Thus, more studies are needed to further explore the validity of this measure by comparing against a reference value. Using SJTs could complement other data collection tools to perform community assessment, and orient the direction of the program in its planning phase.